2019
DOI: 10.3389/fpsyt.2018.00708
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Baclofen as a Treatment for Alcohol Use Disorder: A Clinical Practice Perspective

Abstract: Alcohol use disorder (AUD) is a brain disorder associated with high rates of mortality and morbidity worldwide. Baclofen, a selective gamma-aminobutyric acid-B (GABA-B) receptor agonist, has emerged as a promising drug for AUD. The use of this drug remains controversial, in part due to uncertainty regarding dosing and efficacy, alongside concerns about safety. To date there have been 15 randomized controlled trials (RCTs) investigating the use of baclofen in AUD; three using doses over 100 mg/day. Two addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 123 publications
(188 reference statements)
0
45
0
1
Order By: Relevance
“…59 Of the randomized control trials published on baclofen for alcohol use disorder, none provide analysis based on gender; therefore, further research is needed to study the efficacy and tolerability of baclofen in women. 60 A study evaluating differences between the sexes in alcohol addiction treatment in 380 women and 850 men compared the efficacy of placebo, naltrexone, and acamprosate, or their combination with or without a behavioral intervention. This study found that the percent of days abstinent and time to first heavy drinking day showed the same pattern in both sexes; both naltrexone therapy with medical management and behavioral intervention with medical management had better treatment responses in men and women than those taking placebo or any other individual or combination treatment.…”
Section: Response To Pharmacotherapymentioning
confidence: 99%
“…59 Of the randomized control trials published on baclofen for alcohol use disorder, none provide analysis based on gender; therefore, further research is needed to study the efficacy and tolerability of baclofen in women. 60 A study evaluating differences between the sexes in alcohol addiction treatment in 380 women and 850 men compared the efficacy of placebo, naltrexone, and acamprosate, or their combination with or without a behavioral intervention. This study found that the percent of days abstinent and time to first heavy drinking day showed the same pattern in both sexes; both naltrexone therapy with medical management and behavioral intervention with medical management had better treatment responses in men and women than those taking placebo or any other individual or combination treatment.…”
Section: Response To Pharmacotherapymentioning
confidence: 99%
“…Acamprosate, naltrexone, nalmefene and disulfiram are all approved in one or more region for the treatment of alcohol dependence [38]. Baclofen has been recently approved for AUD treatment in France only for patients who have not responded to other treatments [39].…”
Section: Treatmentmentioning
confidence: 99%
“…To date, most studies of baclofen for SUDs are for AUD, with equivocal results [74][75][76], perhaps partially because potential heterogeneity in treatment response has not been examined. To date, three AUD studies have included neuroimaging during alcohol cue exposure [21,22,24], with modest samples and mixed findings, however, they all emphasize (1) that baclofen's mechanism of action may be through blunting cue reactivity and that (2) more work is needed to understand this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in alcohol dependent smokers seeking treatment for both, baclofen increased the number of days of abstinence of co-use [83]. While both of these preliminary studies show proof of concept for further clinical examination in treatment-seeking cigarette smokers baclofen's efficacy has been challenged [76]. An additional factor that may underlie the mixed therapeutic profile of baclofen is individual response to medication.…”
Section: Discussionmentioning
confidence: 99%